Studi Perbandingan Data Curah Hujan antara Empat Jenis Citra Satelit dan Pengukuran Lapangan di Daerah Bengkulu - Viona Azhari Priscilla; ashar muda lubis; Ella Warahma; Arya J Akbar; Lizalidiawati (Jurnal Teori dan Aplikasi Fisika, 2025)
Bengkulu Province is one of the provinces with high rainfall. High rainfall intensity has a negative impact on various sectors. Therefore, it is necessary to have information regarding accurate rainfall data. Currently there are many satellites that can be used to obtain rain data, this remote sensing technology offers an excellent complement. This research aims to identify comparisons/comparison of rainfall data between various satellite images and field measurements in Bengkulu. The coefficient of determination test was carried out to obtain a correlation between satellite rainfall and direct measurements. Data accuracy analysis shows the correlation results of monthly rainfall from four types of satellite images at 4 observation points in the Bengkulu area. Based on data in the cities of Bengkulu, Kepahiang and Taba Penanjung, it can be seen that the satellite that has the best correlation is the GPM IMERG satellite. For Bengkulu City it was 72.64%, Kepahiang was 74.34% and Taba Penanjung was 56.47%. In the Bukit Kaba area, the best correlation results are on the CHIRPS satellite with a correlation of 15.58%. From the results obtained, we conclude that satellites that can be used by the public and researchers in rainfall analysis are good using GPM IMERG satellite data as a substitute for BMKG data. Keywords: Rainfall, Satellite, correlation.